P816 IBSEN III—a new population-based inception cohort from South-Eastern Norway. (16th January 2018) - Kristensen, V A; Opheim, R; Ricanek, P; Huppertz-Hauss, G; Perminow, G; Detlie, T E; Skram, K; Vatn, S; Olbjørn, C; Rove, J; Stray-Pedersen, R; Ahmad, T R; et al.
Abstract: Background: In the early nineties, Norway reported the highest incidence of inflammatory bowel disease (IBD) worldwide (18.8 per 100000 per year). 1 Subsequently, significant increases in incidence and prevalence have been reported internationally. 2 The primary aim of the IBSEN III study is to estimate the IBD incidence in the South-Eastern Health Region of Norway. In this abstract we present preliminary results from the first 10 months of inclusion. Methods: IBSEN III is an ongoing population-based, prospective, inception cohort in a geographically well-defined area (South-Eastern Health Region of Norway) with a catchment population of three million inhabitants. At time of diagnosis of IBD all adult and paediatric patients will be included during the three year period of 2017–2019 and followed for 5 years. Clinical, endoscopic, demographic and patient-reported data as well as faecal samples for analyses of calprotectin and microbiota are collected from all patients before start of treatment and repeated throughout standardised follow-up. In the three largest hospitals of the region (including a catchment population of one million), additional extensive biobanking is performed in both IBD cases as well as symptomatic non-IBD controls. Results: Based on the IBD incidence from the IBSEN study in the nineties, 555 IBD patients would be expected in the South-Eastern Health Region catchment population in 2017. As of October 31, 2017, 583 IBD patients (including 75 paediatric patients) were included in the study, and 85 symptomatic non-IBD patients were included as controls. Demographics and disease classification in patients with complete clinical data by October 31, 2017 are presented in Table 1. Conclusions: Preliminary data from the IBSEN III study indicate an increasing IBD incidence in South-Eastern Norway. References: 1. Moum B, et al. Incidence of inflammatory bowel disease in southeastern Norway: evaluation of methods after 1 year of registration. Digestion, 1995;56:377–81. 2. Molodecky NA, et al. Increasing incidence and prevalence of the inflammatory bowel diseases with time, based on systematic review. Gastroenterology, 2012;142:46–54.e42.